2019
DOI: 10.1002/bkcs.11690
|View full text |Cite
|
Sign up to set email alerts
|

Negative Thermal Effects on the Structural Order of Methoxy–terminated Mono(Ethylene Glycol) Ethanethiol Self‐assembled Monolayers on Au(111)

Abstract: Self-assembled monolayers (SAMs) on gold surfaces derived from organic thiols provide a very excellent route for preparation of molecular thin films that can be applied to a variety of technological applications. 1-6 SAMs of oligo(ethylene glycol) (OEG)-terminated alkanethiols have been widely used to reduce nonspecific adsorption of biomolecules and proteins 7,8 and control the charge transport of OEG SAM-based molecular electronic devices. 9 The structural order and conformation of OEG SAMs have been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is clear from the STM image that the ordered phase was the dominant phase formed. In contrast, solution-deposited EG2 SAMs at the same preparation conditions (deposition temperature of 323 K and deposition time of 24 h) were dominated by the disordered phase, suggesting that solvent molecules with high thermal energy significantly prevent two-dimensional (2D) ordering of EG2 SAMs at high solution temperature [ 56 ]. Our STM results strongly suggest that the structural order of EG2 SAMs was remarkably enhanced by vapor deposition and high deposition temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear from the STM image that the ordered phase was the dominant phase formed. In contrast, solution-deposited EG2 SAMs at the same preparation conditions (deposition temperature of 323 K and deposition time of 24 h) were dominated by the disordered phase, suggesting that solvent molecules with high thermal energy significantly prevent two-dimensional (2D) ordering of EG2 SAMs at high solution temperature [ 56 ]. Our STM results strongly suggest that the structural order of EG2 SAMs was remarkably enhanced by vapor deposition and high deposition temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, vapor-deposited EG2 SAMs are a bit more loosely packed than solution-deposited SAMs. However, it was found that vapor-deposited EG SAMs at 348 K have much more uniform and well-ordered SAMs compared to solution-deposited EG2 SAMs that contain large areas of disordered phase when formed at 298 K or 323 K [ 39 , 56 ].…”
Section: Resultsmentioning
confidence: 99%